IJCM_215A: Awareness and practices related to the prevention of urinary tract infections among the women of reproductive age group - Mithra Prasanna; Aravind Vijay; Nayak Manasa; Khot Nikita; Silviera Annabelle; Prativadi Jeevitha; Adarsh R (Wolters Kluwer Medknow Publications, 2024)
Background: Urinary Tract Infection is one of the most common bacterial infections that affect women globally. UTI is limited to the lower urinary tract system in most women. Escherichia coli is the most common cause of uncomplicated UTIs. Pre-menopausal women are more susceptible to UTI due to behavioural risk factors. Most of the cases are preventable and assessing the awareness among the women about the risk factors and health behaviour modifications is an important step in this direction. Methodology: Cross sectional study was conducted in hospitals associated with Kasturba Medical College, Mangalore. 188 Women of reproductive age group seeking inpatient, or outpatient healthcare was part of study population. The data was collected using the Interview Schedule which included their demographic details, socioeconomic status, awareness, attitude and practices towards UTI and its prevention. Collected data was entered in SPSS version 16.0 and analysed. Results: Of the total 188 participants in the study, 49.5% were housewives, while 20.7% were semi-skilled workers, 17.5% were professionals, and 12.2% were skilled workers. Of the 61 participants who answered 36% pointed out hygiene as a predisposition to UTI, 29% said they thought decreased water intake had a role to play, 16% thought diet could be a risk factor. 9% felt catheterization is also a cause, 8.9% thought body heat was a probable cause, while 11% said there were other causes involved. According to 96.28% of the participants increased uptake of water was a factor that would help prevent UTI. 1.06% of the women said that regular check-up could help prevent UTI but 48.94% did not see it as a preventive factor. Conclusion: Population on which the study was conducted does know what UTI is, while a few know of the risk factors and complications. It was also seen that the level of personal healthcare they maintain is satisfactory.